Influence of Ads, Product Quality, and Preferences on Honda Purchase Decisions - Umar Burhan; Suharto; Sutiyowati (RTTM, 2025)
This study aims to analyze the influence of advertising, product quality, and consumer preferences on the purchasing decisions of Honda motorcycles in Karanggeneng, Lamongan. The research seeks to understand consumer behavior in vehicle selection. This research employs a quantitative method with data analysis conducted using SPSS. Data were collected through a questionnaire survey distributed to Honda motorcycle users in Karanggeneng. The findings reveal that advertising, product quality, and consumer preferences all significantly affect purchasing decisions, with product quality emerging as the most dominant factor. Validity tests, reliability tests, and other classical assumption tests met the required criteria. These results provide practical insights for motorcycle manufacturers and marketers to enhance their strategies in product development and promotional approaches to better meet the needs of local consumers.